Preparation and Investigation of the Microtribological Properties of Graphene Oxide and Graphene Films via Electrostatic Layer-by-Layer Self-Assembly. (13th August 2015) - Hu, Yongshou; Ma, Haibing; Liu, Wei; Lin, Qianqian; Liu, Bin
Abstract : Graphene oxide (GO) films with controlled layers, deposited on single-crystal silicon substrates, were prepared by electrostatic self-assembly of negatively charged GO sheets. Afterward, graphene films were prepared by liquid-phase reduction of as-prepared GO films using hydrazine hydrate. The microstructures and microtribological properties of the samples were studied using X-ray photoelectron spectroscopy, Raman spectroscopy, X-ray diffraction, UV- vis absorption spectroscopy, water contact angle measurement, and atomic force microscopy. It is found that, whether GO films or graphene films, the adhesion force and the coefficients of friction both show strong dependence on the number of self-assembled layers, which both allow a downward trend as the number of self-assembled layers increases due to the interlayer sliding and the puckering effect when the tip slipped across the top surface of the films. Moreover, in comparison with the GO films with the same self-assembled layers, the graphene films possess lower adhesion force and coefficient of friction attributed to the difference of surface functional groups.